Determinants for not utilizing trachomatous trichiasis surgery among trachomatous trichiasis patients in Mehalsayint District, North-East Ethiopia. - Tedla Desta Meshesha; Goitom Halefom Senbete; Getahun Gebre Bogale (Public Library of Science (PLoS), 2018)
BACKGROUND:Globally, trachoma is the leading cause of infectious blindness. In Ethiopia, the overall Trachomatous Trichiasis (TT) surgical coverage is 41%. Identifying determinants for not utilizing TT surgery among TT patients is important to design and monitor effective intervention programs. Therefore, this study aimed to identify determinants for not utilizing TT surgery among TT patients in Mehalsayint District, North East Ethiopia. METHODOLOGY/PRINCIPAL FINDINGS:A community based unmatched case control study was employed from March 30, 2017 to April 13, 2017. A total of 482 study participants (241 cases and 241 controls) with age of ≥15 years were included in the study. The data were entered with Epi info version 7.2 software and exported to SPSS version 20 for analysis. Bivariate analysis was fitted to screen candidate variables with p<0.2 for the final model. Finally, multivariable logistic regression analysis was employed to identify significant factors (p<0.05) for not utilizing TT surgery. Respondents' age of 16-30 years (AOR: 10.11; 95% CI: 2.72, 37.59) and widowed respondents (AOR: 0.40; 95% CI: 0.21, 0.77), time to reach the service (AOR: 0.46; 95% CI: 0.24, 0.87), unavailability of TT surgeon (AOR: 5.00; 95% CI: 1.16, 21.38), symptoms of trichiasis (AOR: 7.49; 95% CI: 2.41, 23.26), duration of the problem (AOR: 2.56; 95% CI: 1.44, 4.54), the affected eye (AOR: 2.16; 95% CI: 1.23, 3.80), epilation practice (AOR: 3.22; 95% CI: 1.84, 5.64), and place of TT surgery given (AOR: 4.21; 95% CI: 2.48, 7.14) were significant determinants for not utilizing TT surgical services. CONCLUSIONS/SIGNIFICANCE:In this study, TT surgery against trachoma is very low and TT remains public health problem in the district. Being younger age and widowed, time taken to reach the service, absence of TT surgeon, symptoms of trichiasis, duration of problem, the affected eye, epilation practice, and service place were determinants for the inability of TT surgical services. The findings of this study would help in designing effective interventions to reduce trachoma in that district.